Inbreeding and Genetic Differentiation Among Geographic Populations of Lactarius hatsudake in Southwest China - Kuan Zhao; Mingwei Mao; Xianghua Wang; Jianping Xu (Journal of Fungi)
Lactarius hatsudake is an economically important wild edible fungus in sub-tropical and temperate Asia. At present, little is known about its genetic diversity, mode of reproduction, and population structure in natural environments. In this study, we collected 102 specimens from eight geographic locations across three provinces in southwest China. Five simple sequence repeat markers that demonstrated high polymorphism were developed and used to analyze the patterns of genetic variations within and among the eight geographic populations. Analyses of molecular variance revealed that 60% of the observed genetic variation occurred among populations, with the remaining 40% attributable to within populations, while inter-provincial variation was nonsignificant. Combined analyses based on discriminant analysis of principal components, STRUCTURE, and the unweighted pair group method with arithmetic mean identified two distinct genetic subpopulations with each genetic subpopulation showing a wide geographical distribution, a result consistent with ancient divergence and recent gene flow within this species in southwest China. Interestingly, excess homozygosity was observed at most loci in almost all of the eight geographic populations, consistent with inbreeding being common for this species in nature. Together, our results revealed the genetic diversity, mode of reproduction, and geographic structuring of this important wild mushroom in southwest China.